Answer:
-49
-50
Step-by-step explanation:
When a negative number subtracts another negative number, the number becomes positive.
For example: -48-(-49)=1
-48-(-49) becomes -48+49=1
Answer:
1 solution
Step-by-step explanation:
If you were to graph this line it would be a straight line so there is 1 solution.
y=3x
x=y/3
Answer:
37
Step-by-step explanation
Do what is in the parenthesis first
(5)+4^2x(2)
Exponents next
4^2=16
5+16x2
Multiplication next
16x2=32
You're left with the equation 5+32=37
Answer:
C
Step-by-step explanation:
The Answer Is A)11
Explanation: Subtract 3 From Both Sides By 3 Then Divide By 3